2021
DOI: 10.1021/acsnano.1c03508
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Specific Aggregation-Induced Emission Luminogens for Selective Photodynamic Killing of Fungi and Efficacious Treatment of Keratitis

Abstract: The development of effective antifungal agents remains a big challenge in view of the close evolutionary relationship between mammalian cells and fungi. Moreover, rapid mutations of fungal receptors at the molecular level result in the emergence of drug resistance. Here, with low tendency to develop drug-resistance, the subcellular organelle mitochondrion is exploited as an alternative target for efficient fungal killing by photodynamic therapy (PDT) of mitochondrial-targeting luminogens with aggregation-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…The close evolutionary relationship between the mammalian cells and the fungus has always been a matter of concern with many side effects occurring due to similarity in structure. An innovative recent study [170] utilised mitochondrial-targeting luminogens with aggregation-induced emission characteristics (AIE gens) as photosensitizers in place of rose Bengal and riboflavin, which will selectively target the fungal mitochondria, the organelle which has the least potential to develop drug resistance. This comparative study [170] done in a rabbit model compared these AIE gens, namely IQTPE-2O, IQ-Cm and IQ-TPA-assisted PDT with rose Bengal PDT and found it to be less toxic and more efficacious.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…The close evolutionary relationship between the mammalian cells and the fungus has always been a matter of concern with many side effects occurring due to similarity in structure. An innovative recent study [170] utilised mitochondrial-targeting luminogens with aggregation-induced emission characteristics (AIE gens) as photosensitizers in place of rose Bengal and riboflavin, which will selectively target the fungal mitochondria, the organelle which has the least potential to develop drug resistance. This comparative study [170] done in a rabbit model compared these AIE gens, namely IQTPE-2O, IQ-Cm and IQ-TPA-assisted PDT with rose Bengal PDT and found it to be less toxic and more efficacious.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Hence, exploring distinctive AIEgen derived photosensitizers with cell membrane-specic anchoring capability would be signicantly important. [37][38][39][40] Additionally, the nucleus with large amounts of DNA is regarded as the "brain" of the cell, and hence a nucleustargeting photosensitizer could trigger a more effective outcome than that in the cytoplasm. 14 And the level of DNA damage during or aer treatment has a tremendous impact on the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, exploring distinctive AIEgen derived photosensitizers with cell membrane-specific anchoring capability would be significantly important. 37–40…”
Section: Introductionmentioning
confidence: 99%
“…[ 21,31,32 ] Recently, Peng and Zhou et al reported that positive charged AIEgens could treat keratitis, which exhibited excellent photodynamic antibacterial ability and biosafety of ocular applications. [ 33,34 ] According to the previous studies, proper design of cationic AIEgens could specifically discriminate and kill bacteria by PDT over normal cells.…”
Section: Introductionmentioning
confidence: 99%